DYNAMICS OF PHYSICAL QUALITY FORCE OF STUDENTS AT THE TODOR KABLESH-KOV UNIVERSITY OF TRANSPORT AFTER RUGBY-WOMEN TRAINING - D. Peeva (Trakia Journal of Sciences)
To offer of a new sport to students is a reason of new emotions and diligence for improvement. The essence of the new approach is to optimize students' training. The methods used to study the initial and final condition of students include statistical processing and analysis of the obtained data. The results of study have proved the positive impact of applying new and innovative sport in educational process that can be included in the physical education and sport syllabi such as rugbywomen in order to improve fitness of students.